Asystole in an older patient with recurrent falls. Case report - William Fernando Bautista-Vargas (Case Reports)
Introduction: Recurrent falls are a usual problema in older patients. It is therefore important to learn how to differentiate a pathological or syncopal episode from a simple stumbling fall, especially in patients who have limitations for communicating clearly and are poorly understood, in general terms, during the medical consultation. Implantable loop recorders (ILR) have been used as an investigation tool in selected cases of recurrent falls in older patients. Consequently, this case report aims to describe its usefulness in this type of patients.